Achieving Health Equity with e-Healthystrides©: Patient Perspectives of a Consumer Health Information Technology Application - Pemu, Priscilla (Ethn Dis, 2019)
OBJECTIVE: We describe the implementation, clinical outcomes and participant perspectives for e-Healthystrides©. SETTING: Three independent ambulatory clinics and an historic African American (AA) church. PARTICIPANTS: Adults with diagnosed diabetes mellitus type 2. INTERVENTION: e-Healthystrides© health coach facilitated intervention PRIMARY OUTCOME: Acquisition of three new self-management behaviors. SECONDARY OUTCOMES: Blood pressure, blood glucose, A1c, attrition rate and participant perspectives of e-Healthystrides© METHODS: A convergent parallel mixed method design was used in both pilot studies. RESULTS: Two hundred and sixty-four participants, aged ~62±16 years, enrolled. Attrition at 52 weeks varied 50%-90% by site. Low engagement users were defined mainly by anxiety with putting health information online. The primary outcome was achieved in 36% of our participants, with the top 3 self-management behaviors acquired being: reducing risk (24.5%); healthy eating (23.7%); and monitoring (16.4%). Problem solving had the lowest rate of achievement (.91%). Blood pressure improved significantly at all sites at 12 weeks and at clinics A,B,C at 52 weeks. Blood glucose improved at 12 weeks: clinic A (P=.0001), B (P=.003), C (P=.001) and D (P=.03); but, at 52 weeks, only clinics A (P=<.0001) and B (P=.0001). Participants felt empowered by features of e-Healthystrides©. Engagement with health coaches and peers was highly valued. CONCLUSIONS: e-Healthystrides© is effective for self-management behavior change. Participants showed the best success with healthy coping, healthy eating, and monitoring behaviors. They felt empowered by access to health information and valued interaction with coaches and peers. Our findings support strong relational/social network strategy with a role for coaches as guides (apomediaries) who facilitate skill acquisition using technology.